2014
DOI: 10.1104/pp.114.235903
|View full text |Cite|
|
Sign up to set email alerts
|

A Comprehensive Analysis of MicroProteins Reveals Their Potentially Widespread Mechanism of Transcriptional Regulation  

Abstract: Truncated transcription factor-like proteins called microProteins (miPs) can modulate transcription factor activities, thereby increasing transcriptional regulatory complexity. To understand their prevalence, evolution, and function, we predicted over 400 genes that encode putative miPs from Arabidopsis (Arabidopsis thaliana) using a bioinformatics pipeline and validated two novel miPs involved in flowering time and response to abiotic and biotic stress. We provide an evolutionary perspective for a class of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 57 publications
(98 reference statements)
0
28
0
Order By: Relevance
“…Similar small proteins that contain protein-protein interaction domains and that regulate the assembly of functional protein complexes have been termed microproteins, by analogy with the action of microRNAs on mRNAs [16,17]. Microproteins may be as small as 34 aa long and block the assembly of functional transcription complexes [18]. Future functional studies will determine whether the regulatory role of small proteins in the assembly and function of protein complexes is a common mode of action.…”
Section: Big Roles For Small Proteinsmentioning
confidence: 99%
“…Similar small proteins that contain protein-protein interaction domains and that regulate the assembly of functional protein complexes have been termed microproteins, by analogy with the action of microRNAs on mRNAs [16,17]. Microproteins may be as small as 34 aa long and block the assembly of functional transcription complexes [18]. Future functional studies will determine whether the regulatory role of small proteins in the assembly and function of protein complexes is a common mode of action.…”
Section: Big Roles For Small Proteinsmentioning
confidence: 99%
“…Large proteins are easily annotated and more often studied, while shorter proteins tend to be ignored because they pose additional experimental challenges compared to larger proteins. However, with the recent availability of a great array of genome and transcriptome data, an increasing number of SPs have been identified and studied, demonstrating that SPs are widespread and have fundamental functions in all domains of life (Su et al, 2013;Magnani et al, 2014). SPs usually contain a single domain, tend to be nonconventional proteins, and seem to possess lineage-specific or tissue-specific functions (Zhao, 2012;Su et al, 2013).…”
mentioning
confidence: 99%
“…A recent study found a list of potential miPs that show a sequence similarity to TFs but lack a DBD [34]. The authors identified 438 TF-related proteins and referred to these as putative miPs.…”
Section: Tf Synergistic and Antagonistic Interactionsmentioning
confidence: 99%
“…The absence of a domain does not necessarily lead to an inhibitory effect, as evidenced by the two proof-of-concept potential miP candidates that were selected in the above study [34]. The first protein, LITTLE SIPPER (SPPR), is a 52-kDa multidomain protein that regulates HD-Zip IV FLOWERING WAGENINGEN (FWA) [34].…”
Section: Tf Synergistic and Antagonistic Interactionsmentioning
confidence: 99%
See 1 more Smart Citation